2017
DOI: 10.1377/hlthaff.2016.1330
|View full text |Cite
|
Sign up to set email alerts
|

National Health Spending: Faster Growth In 2015 As Coverage Expands And Utilization Increases

Abstract: Total nominal US health care spending increased 5.8 percent and reached $3.2 trillion in 2015. On a per person basis, spending on health care increased 5.0 percent, reaching $9,990. The share of gross domestic product devoted to health care spending was 17.8 percent in 2015, up from 17.4 percent in 2014. Coverage expansions that began in 2014 as a result of the Affordable Care Act continued to affect health spending growth in 2015. In that year, the faster growth in total health care spending was primarily due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 2 publications
1
77
0
Order By: Relevance
“…In the United States alone, healthcare spending accounts for 17.8% of the Gross Domestic Product [33]. Trauma care specifically comprises a significant amount of this expenditure, as it is the leading cause of death for people younger than 44, and the fourth leading cause of death for all age groups in the United States [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States alone, healthcare spending accounts for 17.8% of the Gross Domestic Product [33]. Trauma care specifically comprises a significant amount of this expenditure, as it is the leading cause of death for people younger than 44, and the fourth leading cause of death for all age groups in the United States [34].…”
Section: Discussionmentioning
confidence: 99%
“…The 2006–2008 estimate from the Geisinger Health Study supplement indicated that hypnotics cause roughly 18% of all adult deaths 34 . Considering that about 27% of Medicare costs (U.S. government payments for healthcare of people aged mainly over 65) are incurred in the last year of life, mainly shortly before death, the costs of hypnotics to Medicare in 2015 caused by increased mortality rates could be roughly $31 billion: 0.18 × 0.27 × $646.2 billion 35 . Current U.S. hypnotic prescriptions may be about as frequent as they were in 2006–2008, but current Medicare expenditures in 2017 would be a bit higher.…”
Section: Cost Estimates For Specific Hypnotic Harmsmentioning
confidence: 99%
“…Combined payments for Medicare and Medicaid in 2015 totaled $1.19 trillion, making up 45% of national health expenditures, which total $3.2 trillion. This makes not participating in EMTALA impractical for nearly all hospitals 3. However, the law does not apply to doctors’ offices or clinics, so it has no effect on preventive or primary care.…”
mentioning
confidence: 99%